A high-performance stick-slip piezoelectric actuator achieved by using the double-stator cooperative motion mode (DCMM). (1st June 2022) - Liu, Yanwei; Xu, Zhi; Li, Xuan; Sun, Wuxiang; Huang, Hu
Highlights: A stick–slip piezoelectric actuator with the double-stator cooperative motion mode (DCMM) was proposed. Output performances of the actuator working under the DCMM and STMM were characterized and comparatively analyzed. Under the DCMM, the backward motion was significantly suppressed, resulting in higher speed of the actuator. Compared to the STMM, comprehensive performances of the actuator were significantly improved by using the DCMM. Abstract: Backward motion commonly exists in stick–slip piezoelectric actuators, which deteriorates the comprehensive performances of the actuators and increases the motion nonlinearity. To further improve the comprehensive performances of stick–slip piezoelectric actuators by suppressing the backward motion, a stick–slip piezoelectric actuator working under the double-stator cooperative motion mode (DCMM) was proposed. The structure of the designed actuator and the working principle of the DCMM were addressed in detail. Subsequently, an experimental system was established to characterize the output performances of the designed actuator in terms of motion resolution, angular speed, vertical load, horizontal load, linearity of large-stroke, consistency of forward and reverse motions, and motion stability. Comparative experiments of the actuator operating under the DCMM and the single-stator traditional motion mode (STMM) demonstrated that every output performance of the designed actuator was significantly improved by using the DCMM. For example, the motion resolution was improved from 4.13 μrad to 1.77 μrad, the speed was increased to 1042.99 mrad/s, and the linearity of large-stroke reached 0.99997. Furthermore, compared with some other stick–slip piezoelectric actuators, the designed actuator was extremely competitive in each performance. Experimental results and comparative analysis confirm that using the DCMM, it is feasible to improve the comprehensive performances of actuators, which would broaden the application areas of stick–slip piezoelectric actuators.